Drug Abuse and Psychosis: New Insights into Drug- induced Psychosis - Ham, Suji; Kim, Tae Kyoo; Sooyoung Chung; Im, Heh-In (KOREAN SOC BRAIN & NEURAL SCIENCE, KOREAN SOC NEURODEGENERATIVE DISEASE, 2017)
Addictive drug use or prescribed medicine abuse can cause psychosis. Some representative symptoms frequently elicited by patients with psychosis are hallucination, anhedonia, and disrupted executive functions. These psychoses are categorized into three classifications of symptoms: positive, negative, and cognitive. The symptoms of DIP are not different from the symptoms of schizophrenia, and it is difficult to distinguish between them. Due to this ambiguity of distinction between the DIP and schizophrenia, the DIP animal model has been frequently used as the schizophrenia animal model. However, although the symptoms may be the same, its causes are clearly different in that DIP is acquired and schizophrenia is heritable. Therefore, in this review, we cover several DIP models such as of amphetamine, PCP/ketamine, scopolamine, and LSD, and then we also address three schizophrenia models through a genetic approach with a new perspective that distinguishes DIP from schizophrenia.
Keywords: ESCALATING DOSAGE SCHEDULE; PREPULSE INHIBITION; LATENT INHIBITION; PREFRONTAL CORTEX; GENE-EXPRESSION; WORKING-MEMORY; RECEPTOR HYPOFUNCTION; PYRAMIDAL NEURONS; INDUCED DEFICITS; ANIMAL-MODEL